2016
DOI: 10.5230/jgc.2016.16.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Node-Negative Advanced Gastric Cancer after Curative Gastrectomy

Abstract: PurposeLymph node (LN) metastasis is the best prognostic indicator in non-distant metastatic advanced gastric cancer. This study aimed to assess the prognostic value of various clinicopathologic factors in node-negative advanced gastric cancer.Materials and MethodsWe retrospectively analyzed the clinical records of 254 patients with primary node-negative stage T2~4 gastric cancer. These patients were selected from a pool of 1,890 patients who underwent radical resection at Memorial Jin-Pok Kim Korea Gastric Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The present study also revealed that LBVI+ status was related to poor prognosis in this setting, although it was not an independent prognostic factor. Previous studies revealed that LBVI+ status is associated with poor prognosis after radical surgery for gastric cancer, and is an independent predictor of poor prognosis in patients with negative lymph nodes[18-20].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also revealed that LBVI+ status was related to poor prognosis in this setting, although it was not an independent prognostic factor. Previous studies revealed that LBVI+ status is associated with poor prognosis after radical surgery for gastric cancer, and is an independent predictor of poor prognosis in patients with negative lymph nodes[18-20].…”
Section: Discussionmentioning
confidence: 99%
“…When the LNR was defined as the number of metastatic lymph nodes divided by the retrieved lymph nodes, it was a stronger predictive risk factor for recurrence than the 7 th and 8 th AJCC staging system. Several previous studies of the predictive value of LNR have reported that its use was inconclusive (9,(21)(22)(23). In contrast, other studies showed that LNR was as an independent prognostic factor in gastric cancer (16,17,24,25).…”
Section: Discussionmentioning
confidence: 98%
“…More than half of advanced gastric cancer cases have lymph node metastasis, and lymph node involvement is the most important indicator for survival following a curative resection (R0). Improved survival was observed in node-negative compared to node-positive gastric cancer cases (8,9).…”
Section: Introductionmentioning
confidence: 90%
“…Gastric cancer is the fourth most prevalent cancer in the world 1 , and is the thirdleading cause of cancer-related death worldwide. 2 Although there is a downgrade in incidence and mortality of gastric cancer in Europe, Portugal still remain as one of the most affected European countries, probably due to high prevalence of Helicobacter pylori infection.…”
Section: Introductionmentioning
confidence: 99%